Biblical archaeology: a very short introduction - Cline, Eric H. (Oxford University Press, 2009)
The nineteenth century : the earliest explorers -- Before the Great War : from theology to stratigraphy -- The interwar period : square holes in round tells -- After 1948 : biblical veracity and nationalism -- Beyond the Six-Day War : new surveys and strategies -- The 1990s and beyond : from nihilism to the present -- From Noah and the Flood to Joshua and the Israelites -- From David and Solomon to Nebuchadnezzar and the neo-Babylonians -- From the silver amulet scrolls to the Dead Sea scrolls -- From Herod the Great to Jesus of Nazareth -- From the Galilee boat to the Megiddo Prison mosaic -- Fabulous finds or fantastic forgeries?